Linking local and global: opportunities and challenges for smes – the case of the automotive industry in Mexico - Kraus, Lalita (Redes, 2014)
The focus of the article is on global-local interrelation in a globally integrated system of production, analysed through the Global Value Chain (GVC) framework. The unit of analysis is the small and medium enterprise (SME) as relevant unit when dealing with poverty reduction and distribution. The GVC allows to determine how the SMEs insert themselves in this system and what are the factors that cause a potential suboptimal insertion. The picture is further complicated by specific international agreements (for exemple, TRIPs and TRIMs) and market liberalization. The case of the automotive industry in Mexico exemplifies these risks and helps to better identify the potential role of governmental policies if a better insertion want to be guaranteed and a more equal development promoted.